Collaborative Composition and Urban Popular Music in Digital Music Didactics - Javier F. Merchán-S; Sara González-Gutiérrez (MDPI AG, 2023)
Composition is one of the facets of musical activity that allows a more effective way to interrelate theoretical and practical contents in a real context to enhance the development of creativity and collaborative work in the music classroom. Through a qualitative methodology based on participant observation, the results of several projects aimed at implementing collaborative composition in the training of music teachers at the University of Salamanca through audio production tools (DAW) as a pedagogical strategy to address basic knowledge and specific skills of the curriculum of the music subject in secondary education, are synthesized. From this perspective, this work proposes a structured and sequential model for the collaborative composition of musical productions in the field of popular urban music (with special attention to the rock style), addressing and exemplifying in a practical way issues such as the layered structure in the prototypical song of rock bands, the fundamental rhythmic bases, the harmonic function and the development of chord progressions or the creation and development of melodic lines for the voice.